ISOLATION AND SCREENING OF PHYTATE-DEGRADING YEASTS FROM CEREALS (FUDMA JOURNAL OF SCIENCES, 2025)
Application of phytase (myo-inositol hexakisphosphate phosphohydrolase) to catalyze the release of phosphate from phytates contained on grain-based feed has been used widely. This study was carried out to isolate, identify, screen and produce yeast phytase from cereals using submerged fermentation. Two hundred and twenty seven (227) yeast isolates were obtained from maize, sorghum and millet and identified based on various characteristics such as colony morphology, microscopy, biochemical tests, sugar fermentation tests and molecular analysis. The isolates were then screened for phytase production by growing them on Phytase Screening Medium (PSM) and observing the formation of a clear zone around their colonies, indicating their ability to degrade phytate. It was found that yeast species such as Pichia membranefaciens, Meyerozyma guilliermondii SWS81, Candida krusei, M. guilliermondii M122, Pichia fermentans, M. guilliermondii WM226 and Schwanniomyces occidentalis, were capable of phytate degradation. M. guilliermondii M122, M. guilliermondii SWS81, and M. guilliermondii WM226 with higher solubilizing indices (4.52 mm, 3.64 mm and 5.14 mm respectively) were selected for production and assay. The results showed that crude enzymes from these yeast strains had phytase activity ranging from 44.70 U/mL to 97.70 U/mL, making them potential supplements for animal feeds to improve nutritional status and combat environmental phosphorus pollution.
Keywords: Phytase; Phytate; Yeast; Submerged; Fermentation; Optimization